Physical and chemical properties of soil on selected sugarcane farms in Mt. Nebo, Valencia City, Bukidnon, Philippines (Asian Journal of Agriculture, 2022)
Abstract. Labajo JRN, Pabiona MG. 2022. Physical and chemical properties of soil on selected sugarcane farms in Mt. Nebo, Valencia City, Bukidnon, Philippines. Asian J Agric 6: 79-86. The study was conducted to determine soil's physical and chemical properties on selected sugarcane farms in Mt. Nebo, Valencia City, Bukidnon, Philippines. Soil samples were collected from 24 different sugarcane farms planted with sugarcane following Sloven's Formula for farm selection. Soil samples were collected from August 2018 to April 2019, and the physical and chemical properties of the soil were determined at SPAL, CMU, Musuan, Maramag, Bukidnon, Philippines. Soil texture and percent Water Holding Capacity (%WHC) soil of the sugarcane farms were clayey textured, with %WHC ranging from 54.24-76.30% and bulk Density (BD) and Particle Density (PD) values ranging from 1.05-1.31 Mg m-3 (BD) and 2.28-2.41 Mg m-3, which is ideal for growing sugarcane. Soil samples collected were categorized as medium acidic, marginal in soil organic matter content (SOMC), extractable phosphorus (P) was very deficient, and low on exchangeable potassium (K). That implies these sugarcane farms need soil amendments to meet sugarcane's desired nutrient and pH requirements. Therefore, the sugarcane farms in Mt. Nebo, Valencia City, Bukidnon are required to apply 1.64-7.04 Mg ha-1 of lime and a recommendation rate of 80-200 kg ha-1 Nitrogen (N), 200-500 kg ha-1 of Phosphorus (P), and 170-200 kg ha-1 potassium (K). Moreover, a soil fertility map is necessary to classify and group the delineated soils into map units and capture soil property information to interpret and depict soil spatial distribution on a map.
Keywords: Assessment, Bukidnon, physical-chemical properties, Saccharum officinarum, soil mapping, Valencia City